(untitled) (Economic studies journal, 2021)
Abstract This study aims to display the importance of economic diversification, and knowing its impact on economic growth in Libya during the period (1962-2014), and its used the descriptive analytical approach to analyze diversification and its relationship to economic growth. Hirvendal -Hirschman index was used in order to measure and know the degree of diversification within the Libyan economy for (GDP), exports and revenues. The study found that the Hirschman index in exports and revenues increased, where it was (0.8), (0.6), respectively, which shows the decrease in diversification in them. As for the Hirschman index, it recorded an average value of the (GDP), which amounted to (0.5) This is due to the bad situation of the Libyan economy during the study period. As for econometrics was shown that there was a negative relationship between the Hirschman index and growth, which shows a positive relationship between diversification and economic growth. The output elasticity for diversification reached -0.48, and the model was significant at the level (5 %).